The BarYon Cycle project (ByCycle): identifying and localizing Mg ii metal absorbers with machine learning - Szakacs, Roland; Péroux, Céline; Nelson, Dylan; Zwaan, Martin A; Grün, Daniel; Weng, Simon; Fresco, Alejandra Y; Bollo, Victoria; Casavecchia, Benedetta (Monthly notices of the Royal Astronomical Society, 2023)
The upcoming ByCycle project on the VISTA/4MOST multi-object spectrograph will offer new prospects of using a massive sample of ∼1 million high spectral resolution (R = 20 000) background quasars to map the circumgalactic metal content of foreground galaxies (observed at R = 4000-7000), as traced by metal absorption. Such large surveys require specialized analysis methodologies. In the absence of early data, we instead produce synthetic 4MOST high-resolution fibre quasar spectra. To do so, we use the TNG50 cosmological magnetohydrodynamical simulation, combining photo-ionization post-processing and ray tracing, to capture Mg ii (λ2796, λ2803) absorbers. We then use this sample to train a convolutional neural network (CNN) which searches for, and estimates the redshift of, Mg ii absorbers within these spectra. For a test sample of quasar spectra with uniformly distributed properties ($λ _{\rm {Mg\, {\small II},2796}}$, $\rm {EW}_{\rm {Mg\, {\small II},2796}}^{\rm {rest}} = 0.05\!-\!5.15$ Å, $\rm {SNR} = 3\!-\!50$), the algorithm has a robust classification accuracy of 98.6 per cent and a mean wavelength accuracy of 6.9 Å. For high signal-to-noise (SNR) spectra ($\rm {SNR \gt 20}$), the algorithm robustly detects and localizes Mg ii absorbers down to equivalent widths of $\rm {EW}_{\rm {Mg\, {\small II},2796}}^{\rm {rest}} = 0.05$ Å. For the lowest SNR spectra ($\rm {SNR=3}$), the CNN reliably recovers and localizes EW$_{\rm {Mg\, {\small II},2796}}^{\rm {rest}}$ ≥0.75 Å absorbers. This is more than sufficient for subsequent Voigt profile fitting to characterize the detected Mg ii absorbers. We make the code publicly available through GitHub. Our work provides a proof-of-concept for future analyses of quasar spectra data sets numbering in the millions, soon to be delivered by the next generation of surveys.
Veröffentlicht: 20. September 2023
Gesehen am 26.06.2024